Rattus tanezumi - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Rattus tanezumi (Temminck, 1844) — Oriental House Rat Mus tanezumi Temminck in Siebold, Temminck, and Schlegel, 1844 p.51; Type locality- Nagasaki (restricted by Jones & Johnson, 1965), Japan. Rattus rattus alexandrinus : Kishida & Mori, 1931 p.378; Kuroda, 1938 p.65. R. rattus rattus : Kishida & Mori, 1931 p.378; Won, 1968 p.176. Rattus norvegicus longicaudus Mori, 1937 p.42; Type locality- Ulleung (Dagelet) Island, Korea; Won, 1958 p.449; Won, 1968 p.176. R. tanezumi : Kuroda, 1938 p.69; Musser & Carleton, 2005 p.1489; Kim et al ., 2013 p.550. R . rattus flavipectus : Ellerman, 1949 p.58; Jones & Johnson, 1965 p.390. R. rattus : Ellerman & Morrison-Scott, 1951 p.581; Won, 1958 p.448; Won, 1968 p.176; Yoon, 1992 p.82; Han, 1994 p.47; Won & Smith, 1999 p.28; Han, 2004c p.119; Jo et al. , 2012 p.253. R . alexandrinus : Won, 1958 p.448. R. rattus rufescens : Won, 1967 p.236. Range: The range of R. tanezumi converges in the central and southern regions of Korea, with populations especially prominent in and near port cities including Jeju Island and Ulleung Island (Fig. 125). Interactions with R. norvegicus limit the distribution of the roof rat. On Jeju Island, the range of R. tanezumi was restricted to within 1 km of the port (Won 1967). Remarks: The population on Ulleung Island was mistakenly identified as R . n . longicaudus but corrected as R . rattus tanezumi . Corbet (1978) regarded the Korean population as R . r . tanezumi along with China and Japan. Jones and Johnson (1965) described black rats in Korea as R . rattus flavipectus Won (1967) disagreed and proposed that the black rat in Korea should be R . rattus rufescens . Won (1968) disputed this subspecies with a classification of R. r. rattus instead. Corbet (1978) questioned R . rattus flavipectus stating that R. r. flavipectus was a synonym for R . rattus tanezumi . Koh (1992) confirmed R . r . tanezumi (Temminck, 1844) as the subspecies name for roof rats in Korea. However, Carleton and Musser (2005) elevated R . r . ...